2017
DOI: 10.1002/adsc.201701270
|View full text |Cite
|
Sign up to set email alerts
|

Unified Strategy to Access 6H‐Benzofuro[2,3‐b]indoles and 5,6‐Dihydroindolo[2,3‐b]indoles via UV Light‐Mediated Diradical Cyclization

Abstract: A unified protocol for the construction of 6H-benzofuro[2,3-b]indoles and 5,6-dihydroindolo [2,3-b]indoles via UV light-mediated diradical cyclization was developed and preliminary efforts were also made to functionalize at C10b position of 6Hbenzofuro [2,3-b]indoles. This mild and facile strategy may have great potential in the syntheses of natural products and functional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…(Scheme 27). [22] The authors found that the diradical cyclization efficiently took place when a 250 W high‐pressure Hg UV‐365 lamp was used for irradiation in THF medium with a 6 mM concentration of the reactant. The method could also afford 6 H ‐benzofuro[2,3‐ b ]indoles in addition to the indolo[2,3‐ b ]indoles mentioned in Scheme 27.…”
Section: Methods For the Synthesis Of Indolo[23‐b]indolesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Scheme 27). [22] The authors found that the diradical cyclization efficiently took place when a 250 W high‐pressure Hg UV‐365 lamp was used for irradiation in THF medium with a 6 mM concentration of the reactant. The method could also afford 6 H ‐benzofuro[2,3‐ b ]indoles in addition to the indolo[2,3‐ b ]indoles mentioned in Scheme 27.…”
Section: Methods For the Synthesis Of Indolo[23‐b]indolesmentioning
confidence: 99%
“…While a recurring theme in the synthetic methods has been to employ derivatives of indoles as the starting substrates, [12a,13] authors have also obtained indoloindoles starting from anilines, [5d,14] arynes, [15] or naphthalene derivatives [16] . Indoloindoles may not only be accessed by employing metals such as Cu, [15] Ru, [17] Rh, [18] Pd, [19] or Au, [20] but also in metal‐free aerobic conditions [21] as well as under the influence of UV‐irradiation [22] . There are also methods reported to access densely functionalized indoloindoles in catalyst‐free mechanochemical conditions, [23] thereby highlighting recent synthetic methods’ immense diversity and versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the chemistry of the furoindolines has witnessed an explosive resurgence because of the availability of a concise method for their preparation mediated by metal complexes such as Fe, Ag, Pd, and Cu . Furthermore, metal-free conditions have also been developed, including NIS-, hypervalent iodine­(III)-, electrochemical-, and Bronsted acid-, Lewis acid-, radical-, and organocatalyst-promoted transformations.…”
mentioning
confidence: 99%
“…In the past decades, though oxygenation reactions with molecular oxygen catalyzed by transition metals have been significantly explored, synthesis of oxygen-containing compounds via the directing-group-assisted C–H bond functionalization cascade approaches remain rather rare. As part of our continuing efforts on the cobalt-catalyzed C­(sp 2 )–H bond functionalization reaction assisted by the 2-(1′-methylhydrazinyl)­pyridine (MHP), which is an advantageous bidentate directing group because of its inexpensive access and convenient removal, development of novel synthetic methods for the efficient construction of heterocyclic compounds has been vigorously pursued . We report herein for the first time a unique approach for cobalt-catalyzed trifunctionalization of allenes to afford a series of versatile 3-acylquinoline derivatives.…”
mentioning
confidence: 99%